Assessing the effects of transit oriented development on LRT ridership in Kuala Lumpur - Heidari, Sahar (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Malaysia has been undergoing rapid industrialization and economic growth since the 1970s. Kuala Lumpur, a bustling city in the heart of Malaysia is overwhelmed by traffic jams, where public transport is insufficient to cater to the population and therefore forces most people to drive their own cars. This is worsened by the ever spreading city limits and frequent rain that lashes the city invariably during peak travelling hours.To counter such issues, Transit-oriented development (TOD) can be one of the best solution to traffic congestion. TOD is a mixed-use residential and commercial area planned to maximize access to public transport. Public transport comprising of train and bus service offers a convenient option for people to commute and in the process helps reduce traffic congestion. An effective transit system needs growth pattern and community design that support transit use. It is only complimented by other activities and services located within the vicinity which makes it convenient for the people to commute, run their daily chores without needing a car.The goal of the study is to assess the impact of transit-oriented development on the passenger ridership of LRT based on the current land use development. To achieve this overall aim, a case study TOD which has good transit service is essential for research. A candidate case study mixed use development, the Wangsa Maju station, has been selected. Moreover, Taman Melati station is chosen as a comparative case study for evaluation of the TOD characteristics and the its impact on passenger ridership. Several land use maps and photos prepared to show land use surroundings.The overall observation of results shows that Wangsa Maju has good transit availability and therefore as a TOD represents a worthy case study. This research has found about how various types of land use and levels of density impact transit user. The result shows relation between density and passenger ridership, which take up more density positive effect to the higher LRT ridership. Efficient pedestrian walkway design , transit service and mix land use also relies on will also can be affected to positively to the higher ridership. This research also reviewed the significance and literature related to TOD, its operational attribute, and the extent to which it would help to urban problems in the city roads of Kuala Lumpur.Finally, suggestions were made for further research on topics related to the subject. The recommendations were made from the findings for improving the transit-oriented development activities along transit corridors. Thus, the research fulfilled its aims and objectives and added to the existing knowledge.